Suicide attempts among people who use drugs: a comparative gender-based analysis using the ANRS-Coquelicot survey in France. (3rd September 2022) - Jangal, Candy; Melchior, Maria; de Dinechin, Sébastien; Pannetier, Julie; Jauffret-Roustide, Marie; ,
Abstract: Objective: There exists no national French study on suicide attempts among people who use drugs (PWUD). Our objectives are to analyze lifetime suicide attempts in that population and to compare associated risks based on gender. Method: The ANRS-Coquelicot study (2011–2013) conducted 1718 interviews with people over 18 who have injected or snorted a drug or medication (whether or not it was prescribed) at least once in their lifetime, who speak French or Russian, and who attend harm reduction facilities and drug treatment centers in France. Through stratified multivariate analyses based on gender using a Poisson regression, we determined risk factors. Results: Among PWUD, 39.9% had attempted suicide (n = 655), with a distribution of 58.8% (n = 188) for women and 35.0% (n = 467) for men. Experiences of overdose, depression, receiving psychiatric care, setting during adolescence, daily alcohol use, and number of substances consumed during the last month were risk factors for men. Among women, experiences of overdose, self-reported HIV positive, and daily use of benzodiazepines and cocaine were risk factors. Conclusion: we should develop psychiatric care into health services catering specifically to PWUD. As risk factors differed based on gender, we should strive to create distinct preventive health measures adapted to different populations. Keywords: people who use drugs; lifetime suicide attempts; gender; mental health, quantitative survey